Wall Following Control System with PID Control and Ultrasonic Sensor for KRAI 2018 Robot - Muhamad Hamam Iqbal; Wahyu Sapto Aji (Association for Scientific Computing Electronics and Engineering (ASCEE), 2021)
Indonesian Abu Robot Contest (KRAI) in 2018 with the theme